Methods of wintering yearling steers on dry bluestem pasture, Four-year summary, 1948-52. - Smith, E.F.; Cox, R.F.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
The object of this test was to compare different protein supplements and methods of feeding them to yearling steers on dry bluestem pasture during- the winter. The steers were good to choice quality Hereford yearlings. They were wintered in pastures that were stocked at a normal rate during the previous summer; however, a plentiful supply of dry dead grass was available for each of the lots during the years in which these tests were conducted. From 6 to 19 acres of grass were allowed per steer for the winter. In each year except 1951-52 the steers were purchased in the fall in moderately thin flesh. In 1951-52 the steers were purchased in the spring of 1951 find grazed on bluestem pasture during the summer. In the fall of 1951 when started on this test they carried a moderate amount of flesh. The wintering period of the four-year test extended from mid-December until the latter part of April and averaged 138 days in length.
Keywords: Beef; Bluestem pasture; Protein supplements; Soybean pellets